Effect of Chitosan-Lemongrass Essential Oil-Xanthan Gum Coating on the Shelf Life of White Mushroom (Pleurotus ostreatus) - N. P. Minh (Journal of Global Pharma Technology, 2016)
Mushrooms (Pleurotus ostreatus) are rich in nutrients, such as minerals, vitamins, amino acids, carbohydrate. They have thin and porous epidermal structure with high respiration rate comparing to other fruits and vegetable. They are highly perishable and lose quality very quickly right after harvesting. Mushroom shelf-life is usually short under normal handling and distribution. Therefore, mushrooms must be taken care to maintain their freshness and commercial value. Chitosan has been found to be non-toxic, biodegradable, biofunctional, biocompatible, antimicrobial and antifungal activities. Lemongrass essential oil has stability properties of water vapor permeability of films made based on chitosan. Xanthan gum is one biopolymer promising for food packaging. Our present research focused on the effect of chitosan-lemongrass essential oil-xanthan gum coating on the shelf life of white mushroom (Pleurotus ostreatus). Results revealed that a composite of chitosan-lemongrass essential oil-xanthan gum coating (2.0%: 2.5%: 2.0%) could maintain the quality and extend the shelf-life of mushroom for 7 days of storage.Keywords: Pleurotus ostreatus, chitosan, lemongrass essential oil, xanthan gum, coating, shelf-life